Terracing in Yamuna Ravines for Agricultural Crops - Prajapati, M C; Phadke, A B; Raghuvir, Raghuvir (Annals of Arid Zone, 2016)
Terracing has been one of the most effective erosion control measures in ravine lands. In the coarse soil of Yamuna ravines table-top or level bench terraces have been successfully constructed on very small and small gullies. in the beds of medium and deep gullies and on the hump tops of the three kinds of power viz. bullock-cum-man power, machine-cum- man power and hydraulic-cum-man power used for terrace construction, the machine-cum-man power proved to be the most suitable. Grassed outlets for drops upto 1.5 m with 6:' slopes served well as ramp-cum-waste with. Amongst the masonry outlets the chute spillway with the conduit capable of gently conducting the excess water to the outlet proved to be most suitable for drops upto 4.0 m. Cynodon dactylon grass provided efficient protection to all types of earthen structures. The construction cost during 1958 to 1963 by machine-cum-man power varied from Rs 860.00 to Rs. 4325.00 per hectare depending on quantity of earth work involved. Construction of terraces on medium and deep -gullies is. not advisable due to exhorbitant cost and high degree of instability. The entire capital investment with six percent compound interest can be recovered between f to 6 years through judicious agricultural practices •